A framework for Crosby's quality principles using ISM and MICMAC approaches. Issue 2 (3rd December 2019) - Agrawal, Nishant
Abstract : Purpose: The purpose of this paper is to examine Philip B. Crosby's 14 quality principles and analyze the interaction between them. Hitherto no research has been published on the implementation of total quality management (TQM) using Crosby's 14 principles. To fill this gap, interpretive structural modeling (ISM) and Matrix Impact Cross-Reference Multiplication Applied to a Classification (MICMAC) analysis have been designed to prioritize, sequence and categorize variables to find both the dependence and driving power of these variables. Design/methodology/approach: At the initial stage experts from industry as well as from academia were contacted to provide an input for ISM methodology and examine interactions between identified variables. In this approach, interpretations of the interrelationships among variables have been discussed, whereas MICMAC analysis is used to discover dependence and driving power. Findings: The results of the investigation revealed that "Management Commitment, " "Quality Improvement Team, " "Quality Awareness, " "Supervisor Training, " "Goal Setting" and "Cost of Quality Evaluation" are strategic requirements; "Corrective Action, " "Zero Defects Day" and "Error Cause Removal" are tactical requirements. "Recognition, " "Quality Measurement, " "Quality Councils" and "Do It Over Again" are operational requirements for TQM applications. Originality/value: ISM is used as a part of this research to provide valuable insights into interrelationships among Crosby's quality principles through a systematic framework. The research opens up a new focus area on the implementation of TQM for services as well as for the manufacturing industry.